Pengenalan Huruf L Melalui Lagu dan Kartu Pada Anak Usia 4-5 Tahun dengan Memadukan Bahasa dan Seni: Recognizing the Letter "Ll": Integrating Language and Art - Ummaroch, Riza; Iswatiningsih, Daroe; Salsabila, Nanda; A. H. Zakariah, Fatmawati; Rahmawati, Yeni (J-SES : Journal of Science, Education and Studies, 2025)
This article presents a cheerful and integrated learning method for introducing the letter “Ll” to 4-5 year old students at TK Negeri Bung Karno. The research aims for students to be able to recognize the letter auditorily and visually, and train their ability to find words starting with “Ll”. The learning focuses on two aspects: language (recognizing the letter and finding “Ll” words) and art (sounding out the letter through songs). The method involves introducing the sound through songs and flashcards, word searching, and fine motor activities. Fine motor activities include writing the letter in the air and on a friend's back. The result shows this multisensory approach is effective in helping students enthusiastically recognize the letter and find words. Keyword: letter L; early childhood education; song; language aspect; art aspect; multisensori